Inflective Nano-antenna - Sengor, T. (ELECTROMAGNETICS ACAD, 2012)
In this paper, an antenna structure at nano scale, overcoming the difficulties of including capacitive elements in integrated electronic circuits and devices is developed. The element is based on the wave phenomena around the inflection points on discontinuities of the field. Inflective coordinates are used to overcome the difficulties coming from the inflection points. The simplest case of such discontinuities is created by joining one end point of a convex semicircular thin wire with one end point of a convex semi-circular thin wire where all the end points of both wires trace the same line. The inflective nano-antenna is a extra thin and short wire with an inflection point and has a time varying potential distribution. The deviations of potential of inflective element depend on spatial coordinates on inflective wire.
Keywords: SCATTERING; SURFACES; POINTS; RAYS; Engineering; Physics